Hazard Risk Analysis in the Laboratory of Qolbu Insan Mulia (QIM) Hospital Using the Hazard Identification Risk Assessment and Risk Control (HIRARC) Approach - Ristiawati; Rofiqoh Aulia Ilmi; Imam Purnomo; Yuniarti; Nur Lu’luk Fitriyani; Afif Aditama (HM Publisher, 2023)
Activities in hospitals have risks originating from physical, chemical, biological, ergonomic, psychosocial, and waste factors. Qolbu Insan Mulia Hospital is a health service facility where sick and healthy people gather, which allows work-related accidents and occupational diseases to occur. The laboratory of Qolbu Insan Mulia Hospital is part of the medical support services, which provides hematology, serology, immunology, urine, blood chemistry, drugs, endocrinology, faces, blood transfusion, tumor marker, microbiology, and electrolyte testing services. This study aimed to determine K3 risk management using hazard identification risk assessment and risk control (HIRARC). This research is qualitative research. The techniques used in data collection were field observation, document review, and in-depth interviews. The research results show that in the laboratory there are 17 sources of potential danger consisting of physical, chemical, biological, ergonomic, mechanical, electrical, psychosocial, and waste hazards. In conclusion based on a high-level risk level of 71%, medium 23%, and low 6%, while the control efforts are in the form of administration, manipulation, and PPE.